Swedish election study 1988 - Holmberg, Sören; Gilljam, Mikael; Statistics Sweden (University of Gothenburg, 1991)
This study is part of the collection of Swedish election studies fielded continuously since 1956. Many of the questions are replications of questions asked in previous election studies, but there is also a number of questions not asked in previous surveys. In this study the respondent had to look 10-15 years ahead and to give predictions for the environmental situation, living standard, equality and freedom in Sweden. The respondents were asked how they voted and to give the most important reasons to why they voted on that particular party. They also had to answer how important the following things were for their choice of party: the party´s line of action is good for the respondent´s occupational group; the party has a good party leader; the respondent feels like an adherent of the party; the party´s policy in questions discussed lately is good; the party people are competent and can lead the country; the party´s ideology is good; the respondent always votes with that party. The respondent were asked how they voted at the last two general elections. Respondents who were not voting at the same party were asked for the reason of change, and respondents who voted at the same party were asked if they ever thought of changing party.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Valundersökningen 1988 ingår i serien svenska valundersökningar. Sedan 1956 har en valundersökning genomförts i samband med riksdagsval och folkomröstningar i Sverige.
Många av de frågor som ställdes i studien är replikeringar av frågor som ställts i tidigare valundersökningar, men det finns också ett antal frågor som var nya 1988. Respondenterna ombads bland annat förutsäga situationen för miljön, levnadsstandarden, jämställdheten och friheten i Sverige 10-15 år framåt i tiden. Man tillfrågades också om hur man röstat och de viktigaste anledningarna till att man röstat på detta parti. Man fick även ange hur viktigt följande var för partival: att partiets handlingslinje är bra för respondentens yrkesgrupp, att partiet har en bra ledare, att man känner sig som anhängare till partiet, att partiet för en bra politik i aktuella frågor, att partiet har kompetenta representanter som kan leda landet, att man alltid röstar på detta parti. Respondenterna tillfrågades hur man röstat vid de två senaste valen. De som bytt parti tillfrågades om orsakerna till att man bytt parti och de som röstade på samma parti tillfrågades om man någon gång funderat på att byta parti.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1988
VU88
Keywords: developing countries; utvecklingsland; elections; val; mass media; massmedia; occupations; yrken; participation; deltagande; politics; politik; public sector; offentlig sektor; religion; religion; social mobility; social rörlighet; international relations; internationella relationer; energy; energi; voting intention; röstavsikt; voting; röstning; parliamentary elections; riksdagsval; political interest; politiskt intresse; political behaviour; politiskt beteende; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; party politics; partipolitik; political parties; politiska partier; social policy; politik (policy); political leaders; politiska ledare; election campaigns; valkampanjer; electoral issues; valfrågor; trade unions; fackföreningar; organizations; organisationer; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; minority groups; minoritetsgrupp; lobbying; politisk påverkan; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap